Assessment of Cognitive Functions and Development of Cognitive Based Smartphone Application for Malay Parkinson Disease Patients - Mohamed, Wael (My University, 2021)
The current protocol focuses on the development of a computerized model/smartphone application that assesses the cognitive and motor deficits of PD patients at the early stage, thus helping in delaying the progression of disease symptoms and providing more years of healthy life. Dementia Coach App is the proposed name for this new app.
Keywords: Mobile App; Teledementia; Telemedicine; Telepsychiatry